Based on Slrj.chat.md; inspired by a conversation with aljce
You are a knowledgeable programming languages assistant. You help the user analyze a new programming language.
Aljc is a new programming language. The grammar of Aljc expressions is defined as follows, where x
is any Aljc expression and A
, B
, and C
are atomic values.
x ::= A | B | C | (x x)
The small-step semantics of Aljc are defined by the following rewrite rules, where x -> y
is the relation that x
steps to y
, for some Aljc expressions x
and y
.
(A x) -> x
((B x) y) -> ((y x) x)
(((C x) y) z) -> ((z x) y)
An Aljc expression is evaluated by applying rewrite rules from Aljc's semantics until no more rewrite rules can be applied. The following are some examples of evaluations of Aljc expressions:
(A B)
evaluates toA
((B A) C)
evaluates to((C A) A)
(((C A) A) B)
evaluates toA
What does (((C A) A) B)
evaluate to? Show the evaluation steps.
Let's evaluate the Aljc expression (((C A) A) B)
step by step using the provided rewrite rules.
Given expression: (((C A) A) B)
Step 1: Apply the rule (((C x) y) z) -> ((z x) y)
with x = A
, y = A
, and z = B
.
(((C A) A) B) -> ((B A) A)
Step 2: Apply the rule ((B x) y) -> ((y x) x)
with x = A
and y = A
.
((B A) A) -> ((A A) A)
Step 3: Apply the rule (A x) -> x
with x = (A A)
.
((A A) A) -> (A A)
Step 4: Apply the rule (A x) -> x
with x = A
.
(A A) -> A
No more rewrite rules can be applied, so the evaluation is complete.
Therefore, the Aljc expression (((C A) A) B)
evaluates to A
.
It doesnt the full evaluation correctly!
User
... same as chat1.md except for last line ...
What does
(B A)
evaluate to? Show the evaluation steps.Assistant (Claude 3 Opus)
Great! Let's analyze the evaluation of the Aljc expression
(B A)
using the given small-step semantics.Evaluation steps:
(B A)
- This expression doesn't match any of the rewrite rules directly, so we need to apply the rules to its subexpressions first.Since there are no subexpressions that can be further reduced, we can apply the second rewrite rule:
((B x) y) -> ((y x) x)
. In this case,x
isA
andy
is not provided. So, the expression(B A)
rewrites to((y A) A)
, wherey
can be any Aljc expression.The evaluation cannot proceed further because
y
is not specified. The expression((y A) A)
is the final form after applying the available rewrite rules.Therefore,
(B A)
evaluates to((y A) A)
, wherey
can be any Aljc expression.Comment
Interesting extrapolation, but not exactly sensical according the strict rules.